The programming model of ASSIST, an environment for parallel and distributed portable applications - Vanneschi, Marco (Parallel computing, 2002)
A software development system based upon integrated skeleton technology (ASSIST) is a proposal of a new programming environment oriented to the development of parallel and distributed high-performance applications according to a unified approach. The main goals are: high-level programmability and software productivity for complex multidisciplinary applications, including data-intensive and interactive software; performance portability across different platforms, in particular large-scale platforms and grids; effective reuse of parallel software; efficient evolution of applications through versions that scale according to the underlying technologies. The purpose of this paper is to show the principles of the proposed approach in terms of the programming model (successive papers will deal with the environment implementation and with performance evaluation). The features and the characteristics of the ASSIST programming model are described according to an operational semantics style and using examples to drive the presentation, to show the expressive power and to discuss the research issues. According to our previous experience in structured parallel programming, in ASSIST we wish to overcome some limitations of the classical skeletons approach to improve generality and flexibility, expressive power and efficiency for irregular, dynamic and interactive applications, as well as for complex combinations of task and data parallelism. A new paradigm, called “parallel module” ( parmod), is defined which, in addition to expressing the semantics of several skeletons as particular cases, is able to express more general parallel and distributed program structures, including both data-flow and nondeterministic reactive computations. ASSIST allows the programmer to design the applications in the form of generic graphs of parallel components. Another distinguishing feature is that ASSIST modules are able to utilize external objects, including shared data structures and abstract objects (e.g. CORBA), with standard interfacing mechanisms. In turn, an ASSIST application can be reused and exported as a component for other applications, possibly expressed in different formalisms.